2020
DOI: 10.1186/s13643-020-01424-4
|View full text |Cite
|
Sign up to set email alerts
|

Surgical or non-surgical treatment of traumatic skeletal fractures in adults: systematic review and meta-analysis of benefits and harms

Abstract: Background: A comprehensive overview of treatments of common fractures is missing, although it would be important for shared decision-making in clinical practice. The aim was to determine benefits and harms of surgical compared to non-surgical treatments for traumatic skeletal fractures. Methods: We searched Medline, Embase, CINAHL, Web of Science, and CENTRAL until November 2018, for randomized trials of surgical treatment in comparison with or in addition to non-surgical treatment of fractures in adults. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…e study by Zhang Lu et al demonstrated that targeted management showed significant improvements in eliminating negative emotions, lowering the risk of complications, and relieving pain, which boosted postoperative recovery and ameliorated patients' quality of life. Furthermore, patients receiving targeted management in the present study were more satisfied with the treatment, which indicates that the protocol is feasible [20][21][22].…”
Section: Discussionmentioning
confidence: 84%
“…e study by Zhang Lu et al demonstrated that targeted management showed significant improvements in eliminating negative emotions, lowering the risk of complications, and relieving pain, which boosted postoperative recovery and ameliorated patients' quality of life. Furthermore, patients receiving targeted management in the present study were more satisfied with the treatment, which indicates that the protocol is feasible [20][21][22].…”
Section: Discussionmentioning
confidence: 84%
“…However, the choice of conservative or operative therapy is not only based on age or fracture pattern, but is also influenced by the local bone quality. 9 Poor bone stock is associated with an increased risk for complications such as failure of fixation, secondary dislocation, and malunion, 9,10 and therefore it is essential to include an initial appraisal of the patient’s bone quality.…”
Section: Introductionmentioning
confidence: 99%
“…There is still controversy regarding the optimal internal fixation method for UDCFs. Several meta-analyses have compared the effectiveness and safety of different internal fixation methods for UDCFs [19,[22][23][24][25][26]. However, published meta-analyses did not include combined fixation methods (i.e., LCP + CC) and had a low level of evidence and high heterogeneity among the outcome parameters due to the small number of papers included.…”
Section: Introductionmentioning
confidence: 99%